Vietnam and the East Asian crisis - Leung, Suiwah (Edward Elgar, 1999)
A study of the causes and nature of the 1997 financial crisis in Thailand. It examines the Vietnamese economy and whether it is likely that a banking and currency crisis will spread to Vietnam, concluding that it is unlikely, if a sound financial system and private sector are developed.